2018
DOI: 10.1093/femsec/fiy123
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal communities in boreal forest soil are insensitive to changes in snow cover conditions

Abstract: The northern regions are experiencing considerable changes in winter climate leading to more frequent warm periods, rain-on-snow events and reduced snow pack diminishing the insulation properties of snow cover and increasing soil frost and freeze-thaw cycles. In this study, we investigated how the lack of snow cover, formation of ice encasement and snow compaction affect the size, structure and activities of soil bacterial and fungal communities. Contrary to our hypotheses, snow manipulation treatments over on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 91 publications
8
34
0
Order By: Relevance
“…Both phylum Ascomycota and Basidiomycota were the two dominant phyla in the study site. Similar findings are observed in other cold ecosystems, such as glacier ecosystems, alpine meadows and boreal forests (Yao et al 2013;Antony et al 2016;Gao and Yang 2016;Chen et al 2017aChen et al , 2017bHan et al 2017;Männistö et al 2018). Hypocreales, Archaeorhizomycetales and Eurotiales were the dominant orders in the phylum Ascomycota.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Both phylum Ascomycota and Basidiomycota were the two dominant phyla in the study site. Similar findings are observed in other cold ecosystems, such as glacier ecosystems, alpine meadows and boreal forests (Yao et al 2013;Antony et al 2016;Gao and Yang 2016;Chen et al 2017aChen et al , 2017bHan et al 2017;Männistö et al 2018). Hypocreales, Archaeorhizomycetales and Eurotiales were the dominant orders in the phylum Ascomycota.…”
Section: Discussionsupporting
confidence: 85%
“…As stated above, there might be similar common soil fungal communities among different snowy environments, indicating these fungal communities have an extensive adaptability. A growing number of studies have revealed that snow cover changes leaded to significant impacts on soil fungal community composition and diversity in cold ecosystems (Mundra et al 2016;Semenova et al 2016;Männistö et al 2018). For example, deeper snow cover decreased saprotrophic fungi but increased ECM fungi richness (Mundra et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased snow cover significantly altered the composition of soil fungal communities in arctic tundra (Morgado et al 2016;Semenova et al 2016). In contrast, the lack of snow cover resulted in the slight effects on soil fungal community structure and activity in a boreal coniferous forest (Minna et al 2018). Our results are consistent with the observations found in alpine tundra (Zinger et al 2009) and in temperate and boreal forest ecosystems (Gao et al 2018), which indicated that snow cover change did not induce significant changes in soil fungal diversity and communities composition.…”
Section: Discussionsupporting
confidence: 90%
“…A growing number of studies have revealed that snow cover changes leaded to significant impacts on soil fungal community composition and diversity in cold ecosystems (Mundra et al 2016;Semenova et al 2016;Minna et al 2018). For example, deeper snow cover decreased saprotrophic fungi but increased ECM fungi richness (Mundra et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The three most frequent orders that characterized our regions were the Agaricales, Helotiales, and Russulales (Figure 2). These three groups are generally dominant in boreal forest [11,[53][54][55]. The genus Lactarius and Russula, from the order Russulales, are abundant and diverse ectomycorrhizal fungi in northern forests, especially because there are host generalists [14,56,57].…”
Section: Fungal Diversity In Temperate and Boreal Quebec Forestmentioning
confidence: 99%